The Total Antioxidant Capacity of Foods: A Reappraisal. Application to Commercial Orange Juices - Joël Pincemail; Jessica Tabart; Jean-Olivier Defraigne; Jacques Dommes; Claire Kevers (Journal of Antioxidant Activity, 2015)
Since a few years, more and more attention has been specifically given to dietary antioxidants as agents promoting health and preventing the incidence of diseases. As part of these efforts, analytical methods and assays have been developed to measure the antioxidant content in food substances. In this paper, the antioxidant capacity of 17 orange juices is determined by various assays (DPPH, ORAC, heamolysis, xanthine/xanthine oxidase) as the content in ascorbic acid and total phenolics. The results evidence all the complexity to evaluate the in vitro antioxidant capacity of foods. In very general terms, in spite of the wide utilization in these tests (FRAP, TAC, ORAC TRAP and others), their significance remains obscure. The discrepancy of the results and the absence of good correlation between the assays clearly highlight all the importance of understanding the strengths and weakness of assays evaluating antioxidant potential of a food at the risk of giving erroneous information to the consumer. It is clear that the use of
Keywords: DPPH